Employee Engagement in The Conditions of the COVID-19 Pandemic: Analysis of a Budimex Compaign - Beata TARCZYDŁO (Communications of International Proceedings, 2022)
The motivation for writing the article was the question about the role of campaigns enhancing employee engagement in management practice in the context of the COVID-19 pandemic. The aim of the study is to present campaigns enhancing employee engagement as a management tool of a contemporary marketer, demonstrate a market example, discuss the results of the bibliographical and empirical research carried out, and formulate recommendations for those interested in their application. The aim of the qualitative research conducted in the period from June 2020 to February 2022 was to obtain information on whether and what activities increasing the engagement of employees of the Budimex Group were undertaken during the pandemic and what results they brought. The information search focused in particular on the following problem areas: What activities were carried out? What phenomena/issues do they concern? Who carries them out, for whom, and with whom? What activities do they involve? What results do they bring? The discussion and qualitative research carried out confirmed that campaigns stimulating employee engagement are an important management tool in the context of the pandemic. The Budimex Group’s CSR strategy puts emphasis on employee-oriented activities and involves introducing effective practices as appropriate. The analysed campaign increasing the engagement of employees of a large company during the COVID-19 pandemic concerned important social issues, such as interpersonal relations in the era of remote work, creating opportunities for a better and more healthy lifestyle and work habits, and taking up challenges. The results of the qualitative research have shown that projects oriented at employee engagement are an important human resource management tool in the pandemic crisis and that they effectively motivated employees to take up different activities and brought multiple benefits to all the stakeholders. The literature and empirical studies carried out contribute to expanding knowledge and practical skills in the area of employee engagement management in the time of the pandemic. The campaign carried out, as well as actions, projects, and initiatives implemented with the participation of the employees of the Budimex Group effectively contributed to their engagement in well-being projects for the body, mind, and spirit. In spite of the pandemic, the systematically conducted activities have shown that people are able to take matters into their own hands, carry out amazing projects, and generate benefits for themselves, third parties, and the company. This potential is also significant in the current situation involving the war in Ukraine. The discussed practices enhancing employee engagement may constitute a model to be used by other marketers.
Keywords: employee engagement management; pandemic conditions; campaign and related initiatives with the participation of employees; Budimex’ activities enhancing employee engagement in the context of the COVID-19 pandemic; study results.